1999
DOI: 10.1046/j.1365-2567.1999.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective immune response and severe skin damage following UVB irradiation in interleukin‐6‐deficient mice

Abstract: Interleukin-6 (IL-6), a multifunctional cytokine, is induced in the acute-phase reaction following ultraviolet (UV) irradiation of humans and mice. Using IL-6-deficient (IL-6-/-) mice, we investigated the role of IL-6 in immunosuppression and inflammatory responses caused by UVB (280-320 nm) radiation. The IL-6-/- mice had a defective contact hypersensitivity (CHS) in response to the sensitizers 2,4-dinitrofluorobenzene and oxazolone. The injection of recombinant IL-6 (rIL-6) into these mice resulted in a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 35 publications
4
53
1
Order By: Relevance
“…The finding that IL-6 induces IL-10 production as well as its role in inhibiting IFN-␥ may account for some of its antiinflammatory properties. Nishimura et al (31) have shown that IL-6 promotes IL-10 production using a model of UV-induced skin damage, and our results expand upon that finding by showing that IL-6 can enhance IL-10 production by CD4 and CD8 T cells after injection with schistosome eggs. The enhancement of IL-10 is implicated in the down-regulation of IL-12 seen after the addition of exogenous IL-6 to LN cultures from egg-injected WT mice.…”
Section: Discussionsupporting
confidence: 87%
“…The finding that IL-6 induces IL-10 production as well as its role in inhibiting IFN-␥ may account for some of its antiinflammatory properties. Nishimura et al (31) have shown that IL-6 promotes IL-10 production using a model of UV-induced skin damage, and our results expand upon that finding by showing that IL-6 can enhance IL-10 production by CD4 and CD8 T cells after injection with schistosome eggs. The enhancement of IL-10 is implicated in the down-regulation of IL-12 seen after the addition of exogenous IL-6 to LN cultures from egg-injected WT mice.…”
Section: Discussionsupporting
confidence: 87%
“…UVB irradiation induces inflammatory cytokines, such as interleukin-1, interleukin-6, and TNF-α (27)(28)(29)(30)(31)(32). Inflammation induced by UVB irradiation produces erythema (14) and subsequently leads to cutaneous hypertrophy (31).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation by UV-B irradiation causes cutaneous hypertrophy (18). In addition, UV-B irradiation induces inflammatory cytokines such as interleukin-6 and TNF-α (19)(20)(21). Aggrecan may act with the immune system and inhibit inflammatory cytokines as an active anti-aging component.…”
Section: Discussionmentioning
confidence: 99%